Comparison of Shear Strength of Metal and Ceramic Orthodontic Brackets Cemented to Zirconia Depending on Surface Treatment: An In Vitro Study - Cetik, Sibel; Ha, Thaï Hoang; Sitri, Léa; Duterme, Hadrien; Pham, Viet; Atash, Ramin (European Journal of Dentistry, 2019)
Objectives Due to the high demand for all-ceramic restorations, monolithic zirconia restorations are nowadays frequently used. With the demand for adult orthodontic treatments, orthodontists need to be mindful of the quality of their brackets bonding to this type of material, as it requires special conditioning. This study aimed to compare different surface treatments of zirconia when bonding metal or ceramic orthodontic brackets. The objectives are to compare the shear bond strength; the amount of adhesive remaining on the surface of the material; the incidence of adhesive, cohesive, and mixed failures; and the occurrence of zirconia fractures.Materials and Methods Forty monolithic blocks of zirconia of a diameter of 10 mm and a length of 10 mm were prepared and randomly divided into two groups (n = 20): metallic or ceramic brackets. Each group was subsequently divided into two subgroups (n = 10) depending on the surface preparation (laser treatment or airborne particle abrasion): SMB (airborne particle abrasion, metal bracket), SCB (airborne particle abrasion, ceramic bracket), LMB (laser; metal bracket), and LCB (laser, ceramic bracket). The samples were tested for shear bond strength using a universal testing machine. The adhesive remnant index and the occurrence of zirconia fractures and different types of failures were assessed by optical and electron microscopy.Statistical Analysis Results were analyzed using analysis of variance.Results The differences were significant between the metallic (SMB, LMB) and ceramic (SCB, LCB) bracket groups with regard to shear bond strength, with respectively 23.29 ± 5.34 MPa, 21.59 ± 4.03 MPa, 20.06 ± 4.05 MPa, and 17.55 ± 3.88 MPa. In terms of surface treatment, no statistical differences were found between the different groups.Conclusion Metal brackets have a greater bond strength than ceramic brackets when cemented to zirconia. The surface treatment of zirconia surface has no influence on the shear bond strength.
Keywords: zirconia; brackets; cementation; surface treatment